2019
DOI: 10.1021/acs.energyfuels.9b01832
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N,O-Doped Porous Graphene from Petroleum Coke for Deep Oxidative Desulfurization of Fuel

Abstract: Efficient metal-free carbon-based catalysts are of particular interest due to their unique electronic structure and compositional variability. Herein, petroleum-coke-based N,O-doped porous graphene (PG) was prepared as a preferred alternative to metal catalysts for catalytic oxidative reaction. Such a high specific surface area and heteroatom-rich structure promote high exposure of active sites, regulating the electron delocalization of materials effectively. In addition, the synergistic effect between N-doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…To address environmental friendliness and sustainability, He et al reported a creative and sustainable technique to derive N,O-doped porous graphene (N,O-PG) from the coke waste of the petroleum refinery industry. 199 Basically, a ball-milling process was first conducted in the presence of coke and urea, accompanied by annealing to activate the catalyst and decompose the layered structure graphene into an ultrathin nanosheet structure (Fig. 17a).…”
Section: Application Of Metal-free Nanomaterials In Odsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address environmental friendliness and sustainability, He et al reported a creative and sustainable technique to derive N,O-doped porous graphene (N,O-PG) from the coke waste of the petroleum refinery industry. 199 Basically, a ball-milling process was first conducted in the presence of coke and urea, accompanied by annealing to activate the catalyst and decompose the layered structure graphene into an ultrathin nanosheet structure (Fig. 17a).…”
Section: Application Of Metal-free Nanomaterials In Odsmentioning
confidence: 99%
“…203 First, the activation of H 2 O 2 was stimulated by the carboxyl groups at the edge of GO. After DBT oxidation, the produced polar DBT sulfone strongly chemisorbed on the basal plane of GO, which contained hydroxyl groups, via hydrogen bonding and p-p interactions, thus eliminating the need for solvent to separate 199 Copyright 2019, American Chemical Society. (c) Proposed route for the oxidation of DBT with H 2 O 2 by GO with a SEM image of GO.…”
Section: Application Of Metal-free Nanomaterials In Odsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the carbon material can be ascribed to the presence of defect sites on its surface, its developed surface area, or the presence of surface groups. Here, we propose the mechanism displayed in Figure 10 for the ODS of sulfur-containing compounds according to different proposals in the oxidation activity of carbon catalysts [130,131].…”
Section: Carbon Catalysts On Their Ownmentioning
confidence: 98%
“…This interaction between acidic groups and S atoms increases the physisorption of S compounds in the AC structure [133]. [131] studied the influence of doping GO with nitrogen and oxygen for the aerobic ODS of various sulfur compounds. They compared two GO samples.…”
Section: Carbon Catalysts On Their Ownmentioning
confidence: 99%